(untitled) - Brownlee, Adam; Adam Brownlee (Hoboken, N.J.)
The guide to making money the Warren Buffett way The book that presents the same fundamentals that Warren Buffet used to turn an initial 105,000 USD investment into a 40 USD billion fortune in a way the general reader can apply, Building A Small Business that Warren Buffett Would Love is a succinct, logical, and straightforward guide to financial success. Highlighting one simple message: that Warren Buffett successfully invests in great businesses with strong fundamentals, it argues that these fundamentals can be replicated in a small business to yield outstanding results
Includes bibliographical references and index
Keywords: Buffett; Warren; Small business; Investments; Small Business